Lyapunov-designed super-twisting sliding mode control for wind energy conversion optimization - Evangelista, Carolina Alejandra (2013)
This work explores an adaptive second-order sliding mode control strategy to maximize the energy production of a wind energy conversion system (WECS) simultaneously reducing the mechanical stress on the shaft. Such strategy successfully deals with the random nature of wind speed, the intrinsic nonlinear behavior of the WECS, and the presence of model uncertainties and external perturbations acting on the system. The synthesized adaptive controller is designed from a modified version of the super-twisting (ST) algorithm with variable gains. The suitability of the proposed strategy is proved by extensive computer-aided simulations employing a comprehensive model of the system emulating realistic conditions of operation, i.e., considering variations in the parameters and including external disturbances. Additionally, a second controller based on the traditional ST algorithm is also designed and simulated. Results are presented and discussed in order to establish a comparison framework.